Getting programs of life adjustment education under way : suggestions for state committees on life adjustment education working in cooperation with state departments of education / prepared by Howard R. Anderson ; in collaboration with the Office Consultants on Life Adjustment Education ; sponsored by the Commission on Life Adjustment Education for Youth ... (1949)
Summary goes here